Leadership Development through the 'My Decisions' Program: A Cross-Sectional Study in the Kurdistan Region - Vanya Ibrahim Jwamer; Zana Ahmad Qasab; Jaafar Omer Ahmed (Journal of Philology and Educational Sciences, 2025)
Leadership is a changing process of affecting and directing individuals or group of people to reach common goals. The "My Decisions Course" (MDC) is a structured-academic program that explains essential life and work skills like planning, time management, communication, and leadership. This research explores that how MDC affects the skills that participants learn and how they use those skills in their personal and professional lives. Descriptive cross-sectional study was utilized with graduates of the MDC program in Kurdistan Region of Iraq. The participants of this research were chosen based on convenience sampling method. Data were collected via a structured questionnaire developed by the researchers and distributed electronically. Descriptive statistics and chi-square tests were used to analyze the data, with significance set at p ≤ 0.05. Among the 67 participants, 73.1% considered having followers as a key leadership requirement, and 91% emphasized the importance of communication for effective leadership. Regarding planning, 56.7% reported they always try to overcome obstacles, and 49.3% agreed that planning plays a significant role in decision-making. Furthermore, 64% stated that planning skills support them in organizing their lives and managing their time effectively. The MDC program has a positive impact on developing participants’ leadership, planning, and time management skills. These findings underscore the importance of structured leadership development courses in cultivating essential life competencies.